Solar System Astrophysics - Milone, Eugene F. (Springer, 2017)
Solar System Astrophysics opens with coverage of the atmospheres, ionospheres and magnetospheres of the Earth, Venus and Mars and the magnetosphere of Mercury. The book then provides an introduction to meteorology and treating the physics and chemistry of these areas in considerable detail. What follows are the structure, composition, particle environments, satellites, and rings of Jupiter, Saturn, Uranus and Neptune, making abundant use of results from space probes.